2021
DOI: 10.1111/hsc.13420
|View full text |Cite
|
Sign up to set email alerts
|

In the midst of plenty: Experiences of food insecurity amongst women living with HIV in Vancouver, Canada

Abstract: Globally, people living with HIV (PLWH) are disproportionately affected by food insecurity. Yet there is limited understanding of the impacts of food insecurity among cisgender and transgender women living with HIV (WLWH) in high‐income countries. Thus, it is critical to examine the lived experiences of WLWH and food insecurity to inform policy and service provision. As part of the community‐based SHAWNA (Sexual Health and HIV/AIDS: Women's Longitudinal Needs Assessment) study, we conducted 64 semistructured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 52 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…This may result in PLHIV needing to apply for social assistance to access comprehensive ART coverage [11,12]. Limited income from social assistance, lowwage employment and illness-related loss of income among employed PLHIV produce challenges acquiring and maintaining sufficient, reliable food and housing [3,[11][12][13][14]. This is not unique to Canada-socio-economic challenges, including food and housing insecurity, low income and unemployment, were also reported in a review of PLHIV in other high-income contexts, such as the United States, Australia and the United Kingdom [10].…”
Section: Introductionmentioning
confidence: 99%
“…This may result in PLHIV needing to apply for social assistance to access comprehensive ART coverage [11,12]. Limited income from social assistance, lowwage employment and illness-related loss of income among employed PLHIV produce challenges acquiring and maintaining sufficient, reliable food and housing [3,[11][12][13][14]. This is not unique to Canada-socio-economic challenges, including food and housing insecurity, low income and unemployment, were also reported in a review of PLHIV in other high-income contexts, such as the United States, Australia and the United Kingdom [10].…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study reported that only 27.4% of women living with HIV were food-secure, compared with 88.6% of the general population [34]. A second study of women living with HIV in Vancouver, Canada, showed high rates of food bank utilization [22], which may not provide all varieties of nutritious foods. Our finding that non-white women had lower odds of adequate dietary vitamin D intake may also be a reflection of food insecurity, which is more prevalent among racialized groups in Canada [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary/supplemental intake, therefore, becomes important for these women. Women living with HIV may also experience barriers to intake from food and supplements, as they often experience food insecurity [22], low incomes [23] and housing instability [23]. Furthermore, women living with HIV commonly take multiple medications in addition to antiretrovirals, which may result in 'pill fatigue' and a reluctance to take supplements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity may facilitate a greater reliance on abusive partners, and precarious work and housing situations, which can increase the likelihood of violence (Conroy et al, 2019). Evidence suggests that social assistance and food banks are inadequate responses to food insecurity and calls for structural changes to address food insecurity (Sernick et al, 2021). Furthermore, the American Dietetic Association and Dieticians of Canada emphasize the importance of diet and food security when taking ART to support optimal health and well-being (American Dietetic Association and Dietitions of Canada, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Community-based organizing has successfully implemented food security initiatives to provide accessible and nutritious food beyond traditional foodbanks (Kirbyson, 2006). It is critical that similar initiatives be supported and designed with women living with HIV, with options for low-barrier, gender-specific, confidential access (Sernick et al, 2021).…”
Section: Discussionmentioning
confidence: 99%